2019
DOI: 10.1371/journal.pone.0214092
|View full text |Cite
|
Sign up to set email alerts
|

Associations between Walk Score and objective measures of physical activity in urban overweight and obese women

Abstract: The purpose of this study was to examine associations between the Walk Score and physical activity in young, overweight/obese urban women. Project Health included 45 White or African American women (BMI 31.5±3.9 kg/m 2 ; age 26.5±4.6 years; 62% African American) living in the Boston area. An accelerometer estimated steps/day and mins/day in light physical activity (100–2019 counts-per-minute) and moderate-to-vigorous-physical activity (≥2020 cpm). Walk Score was used to estimate the walk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“…In the present study, we added the Walk Score, which is associated with the number of steps per day, minutes of leisure walking, and daily moderate- to vigorous-intensity physical activities [ 27 , 28 , 29 ], to the covariates; however, future studies should add a method for the accurate measurement of the actual walking intensity and duration. We used the LTCI system for disability incidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present study, we added the Walk Score, which is associated with the number of steps per day, minutes of leisure walking, and daily moderate- to vigorous-intensity physical activities [ 27 , 28 , 29 ], to the covariates; however, future studies should add a method for the accurate measurement of the actual walking intensity and duration. We used the LTCI system for disability incidents.…”
Section: Discussionmentioning
confidence: 99%
“…Neighborhood walkability is associated with participation in physical and social activities by older adults [ 24 , 25 , 26 ]. The Walk Scores are associated with the number of steps per day, minutes of leisure walking, and daily moderate- to vigorous-intensity physical activities [ 27 , 28 , 29 ]. The Walk Score was calculated for all participants using their home addresses.…”
Section: Methodsmentioning
confidence: 99%
“…Additionally, individuals with obesity took approximately 1,500 steps fewer than those with normal BMI (Bassett et al, 2017). Although a recent, small study of young, overweight urban women (62% African American) reported an overall average of 14,143 steps per day, the unexpectedly high step count is likely attributable to the young age (mean = 26.5 years), highly walkable urban environment (Boston, MA), racial heterogeneity (38% European American), lower BMI (mean = 31.5 kg/m 2 ), and use of a waist-worn accelerometer rather than Fitbit device (Camhi et al, 2019). Despite prior work demonstrating significantly different step counts based on individual characteristics such as age and BMI (Sisson, Camhi, Tudor-Locke, Johnson, & Katzmarzyk, 2012), our mixed-effects modeling at the week level did not identify any significant individual characteristics in the relationship with steps.…”
Section: Discussionmentioning
confidence: 99%
“…Walkability has been defined as the degree to which the neighborhood environment can accommodate pedestrians’ activities ( 17 ). In a walkable neighborhood, walking activity is safe and encouraging ( 18 ) because of the built environmental features such as street connectivity, the presence of walking facilities, the proximity of shops and services, and residential density ( 19 ). Distance and walking time from home to school, either as an objective measure (based on direct observation of trips or using Geographic Information System [GIS] data) or subjective measure (based on individuals’ perception derived from surveys) have been identified as significant barriers for children’s active travel to school ( 20 ).…”
Section: Introductionmentioning
confidence: 99%